2004
DOI: 10.1038/sj.ijir.3901179
|View full text |Cite
|
Sign up to set email alerts
|

Cost implications of sexual dysfunction: the female picture

Abstract: This study examined the clinical workload, outcome and direct costs of managing women with sexual dysfunction in an NHS clinic in the UK. A retrospective analysis of a 3-month period showed that of 47 referrals to the clinic, 38 undertook treatment. The therapists' assessments suggested that over 80% of patients improved on treatment. The average cost per patient was d472 (compared to d335 per annum for erectile dysfunction, which included physician's and drug costs). The average cost by type of practitioner w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For example, one publication (excluded from the current review as is was not published in English) estimated that in Germany the direct and indirect costs associated with urinary incontinence following prostatectomy are approximately EUR 71.8 million [73]. Similarly, figures from the UK estimate that on a per patient level, the annual cost of erectile dysfunction is GBP 335 [74].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one publication (excluded from the current review as is was not published in English) estimated that in Germany the direct and indirect costs associated with urinary incontinence following prostatectomy are approximately EUR 71.8 million [73]. Similarly, figures from the UK estimate that on a per patient level, the annual cost of erectile dysfunction is GBP 335 [74].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the inadequacies in the basic medical health services for sexual problems are not compensated by an adequate specialized service. Patients have been forced to tolerate a long waiting list for treatment (Goldmeier et al, 2004), or pay high costs for private treatment, or look for alternative or folk methods of management with little scientific basis (Ko, 2003).…”
Section: Treatment Problemsmentioning
confidence: 99%
“…A study by Goldmeier, Malik, Phillips, and Green (2004) investigated the cost of female sexual dysfunction for the NHS each year. Results showed that treatment was beneficial with 80% of patients reporting an improvement in their symptoms.…”
Section: Treatment Problemsmentioning
confidence: 99%
“…Goldmeier and colleagues calculated that, in 2004, the average costs of the treatment of sexual dysfunctions in the UK for women were €417 when delivered by a psychologist and €896 when delivered by a sex therapist [26]. Potentially, a certain proportion of patients with sexual problems do not require this type of intensive and costly treatment, but can adequately and satisfactorily be treated with less intensive and lower-cost alternatives.…”
Section: Introductionmentioning
confidence: 99%